Efectividad de un programa de cuidado y manejo de la voz, en docentes de dos instituciones educativas de la ciudad de Cartagena (2018)
OBJECTIVE: To measure the effectiveness a program of promotion and prevention to avoid the alterations in qualities of voice in teachers of two educational institutions from Cartagena METHODOLOGY: This investigation is experimental type because we made a program of promotion was implemented for the care of the vocal health and prevention of the alterations in qualities of the voice. RESULTS:The most frequent age in the population was between 25 and 75 years old, being more frequent the age from 35 to 40 years old with 33,33 %. The predominant gender was the female with 83,33 % unlike the male with 16,67 %, as for distribution of the teachers according to the sensation during the work there were obtained the sensation during the work over more predominate were different relating to: excessive use of the voice, noise in the environment that it impedes to speak, difficult to breathe, pain and sorethroat, with 90,00 % in comparison of 1,33 % who did not present any sensation of inconvenience during the work. The data analysis demonstrated low significant changes to level in the qualities of the voice of teachers later to the application of the program, nevertheless a variation was observed in the degree of severity of the alteration in the qualities of the voice...